Ban policy on nickel as natural resources from the perspective of mashlahah by Imam Al-Ghazali - Ika Wulandari; Dwi Fidhayanti (UIN Siber Syekh Nurjati Cirebon, 2024)
This study examines Indonesia’s policy of restricting nickel exports and its implications, focusing on the state’s approach to enhacing the value of nickel through downstream processes. It adopts a normative juridical research method with a legislative approach, utilizing primary, secondary, and tertiary legal materials. Legal sources are gathered through literature review and internet study, and analyzed using deductive and descriptive reasoning methods. Based on relevant analysis and discussions, the study concludes that Indonesia’s export restrictions primarily aim to improve nickel quality through downstream processing line with principles of prosperity and economic welfare. Despite concerns about potential limitations, such as the impact of smelter construction on local communities, Indonesia’s policy remins consistent with international trade principles to support domestic economic growth and job creation. Future research should comprehensively address these obstacles provide a deeper understanding of the socio-economic implications of nickel export restrictions and downstream development in Indonesia.Keywords: Nickel; Natural resources; Maslahah